Klasifikasi Kelayakan Kualitas Air Tanah Kota Surabaya Menggunakan Fuzzy Tipe Mamdani - Nengse, Sulistiya; Dian Candra Rini Novitasari (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Surabaya is the second largest city in Indonesia which is densely populated. The need for fresh water for the population of Surabaya is 4.61 m3/second, where many still use groundwater as a source of clean water. In this research, groundwater feasibility test will be carried out using 6 parameters at 31 points in the city of Surabaya. The water quality parameters to be tested are turbidity, temperature, pH, hardness (CaCO3), E. coli bacteria, and Dissolved Oxygen. The method used in the classification of ground water feasibility is the Mamdani method because it has a broad field coverage and is easily understood by humans. The results showed that the average quality of groundwater in the city of Surabaya was: turbidity 2.34 NTU, temperature 28.6 oC, pH 7.4, hardness (CaCO3) 349.67 mg/liter, and E. coli bacteria 0,13 CFU/100 ml, and DO 1.93 mg/l. The results of the evaluation of the feasibility of groundwater are compared with water quality parameters for hygiene and sanitation purposed based on PerMenKes No. 32 of 2017, all parameters have met the quality standards and are suitable as a source of clean water except for the parameter of E. coli bacteria. Based on the modeling using Fuzzy Mamdani type, there are ten sampling points that have groundwater that is not suitable as a source of clean water. Management recommendations for the protection of groundwater resources in the city of Surabaya for the community and for decision making by the government are disinfection using chlorine.